Determinants of the New Zealand Yield Curve: Domestic vs. Foreign Influences - Enzo Cassino; Neil Cribbens; Tugrul Vehbi (New Zealand Government, The Treasury, 2014)
This paper examines the relationship between the New Zealand government yield curve and the contribution of global and domestic factors influencing it. We apply the Nelson and Siegel method, which has been widely used internationally for fitting a yield curve, to decompose it into three independent factors – level, slope and curvature. We then analyse the link between each New Zealand yield curve factor, the global factors and observable domestic and international macroeconomic variables. We find that approximately half the movement in the level factor for New Zealand, which drives the yield curve at long maturities, is explained by the global level factor. Meanwhile, the global slope factor explains around a third of the movement in New Zealand's slope factor. Of the remaining domestically driven components, it is difficult to identify a significant role for any specific domestic macroeconomic variables. However, domestic variables have a larger impact on the slope and curvature factors as shorter maturities are more directly under the control of the monetary authority and react to macroeconomic fundamentals. The output gap in particular is highly relevant in explaining the slope of the yield curve.
Keywords: G1; E4; C5; 330; Term structure; Interest rate; Global yield; Dynamic factor model; Öffentliche Anleihe; Zinsstruktur; Neuseeland